Case Report: Intravascular Large B-Cell Lymphoma: A Clinicopathologic Study of Four Cases With Review of Additional 331 Cases in the Literature - Han, Yingying; Li, Qingjiao; Wang, Dan; Peng, Lushan; Huang, Tao; Ou, Chunlin; Yang, Keda; Wang, Junpu (Frontiers in Oncology, 2022)
Intravascular large B-cell lymphoma (IVLBCL) is a rare and highly malignant non-Hodgkin B-cell lymphoma with uncommon clinical presentation and poor prognosis. The diagnostic pitfall of IVLBCL is mainly due to the fact that subtle histological changes could be easily overlooked, in addition to its rare occurrence, nonspecific and variable clinical presentations, and the absence of significant mass lesions. The purpose of this study is to further explore the clinicopathologic and molecular features of IVLBCL to ensure an accurate diagnosis of this entity. Here, we retrospectiv ely present the data of the four new cases and the literature cases. The age ranged from 23 to 92, with a medium age of 67 and a male to female ratio of 1:1. The clinical manifestations are extremely variable, including fever, night sweats and weight loss, anemia, thrombocytopenia, unexplained hypoxemia, impaired consciousness, and skin lesions, as well as the extremely low levels of serum albumin, high levels of serum lactate dehydrogenase (LDH), soluble interleukin 2 receptor (sIL2R) and ferritin. Morphologically, 99.9% of cases showed a selective growth pattern with large, atypical lymphocytes within the lumen of small blood vessels. In addition, vast majority of cases were positive for CD20, CD79a, PAX5, MUM1 and BCL6, and a subset of cases expressed BCL2 and CD5, while CD3 and CD10 were typically negative. Ki-67 proliferative index ranged from 20% to 100%. To sum up, we have conducted comprehensive case reports, to the best of our knowledge, this is the largest reported cohort of IVLBCL cases. Comprehensive assessments and more IVLBCL cases are required for early diagnosis and prompt treatment.